2007
DOI: 10.1016/j.molcel.2007.05.030
|View full text |Cite
|
Sign up to set email alerts
|

E2F Activation of S Phase Promoters via Association with HCF-1 and the MLL Family of Histone H3K4 Methyltransferases

Abstract: E2F transcriptional regulators control human-cell proliferation by repressing and activating the transcription of genes required for cell-cycle progression, particularly the S phase. E2F proteins repress transcription in association with retinoblastoma pocket proteins, but less is known about how they activate transcription. Here, we show that the human G1 phase regulator HCF-1 associates with both activator (E2F1 and E2F3a) and repressor (E2F4) E2F proteins, properties that are conserved in insect cells. Huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
321
3
2

Year Published

2010
2010
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 225 publications
(341 citation statements)
references
References 54 publications
15
321
3
2
Order By: Relevance
“…MOZ is also associated with other transcription factors such as RUNX2, C/EBPa, C/EBPb, c-Jun, NF-kB, Nrf2/MafK and p53 (Pelletier et al, 2002;Ohta et al, 2005Ohta et al, , 2007Katsumoto et al, 2006;Chan et al, 2007;Rokudai et al, 2009). In addition, it was reported that MLL is a protein partner of p53 and HCF-1 in a cell cycle-dependent manner (Tyagi et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…MOZ is also associated with other transcription factors such as RUNX2, C/EBPa, C/EBPb, c-Jun, NF-kB, Nrf2/MafK and p53 (Pelletier et al, 2002;Ohta et al, 2005Ohta et al, , 2007Katsumoto et al, 2006;Chan et al, 2007;Rokudai et al, 2009). In addition, it was reported that MLL is a protein partner of p53 and HCF-1 in a cell cycle-dependent manner (Tyagi et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…H3K4 methylation is primarily localized in the promoter and regulatory regions of genes. Some transcription factors, such as Menin, LEDGF, HCF1/2, E2F, NFE2, p53, and c-Myb, have been shown to interact with MLL family members, which could lead to methylation of H3K4 in a locus-or DNA sequence-specific manner [16,17,[25][26][27][28][29]. A recent study by our group identified a physical and functional interaction between RUNX1 and MLL, and showed that both are required for maintenance of the H3K4me3 mark at two critical regulatory regions of the RUNX1 target gene PU.1 locus [30].…”
Section: Mll and Its Role In Normal Hematopoiesismentioning
confidence: 99%
“…HCF-1 was initially identified as a human coactivator for immediate-early gene expression of herpes simplex virus (HSV) by forming a complex (VP16-induced complex, VIC) with the HSV protein VP16 and the cellular transcriptional regulator Oct-1 (1). HCF-1 regulates cell-cycle progression by mediating associations between DNA-binding transcription factors and chromatin modifying complexes (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12).…”
mentioning
confidence: 99%